Free convection of a suspension containing nano-encapsulated phase change material in a porous cavity; local thermal non-equilibrium model. Issue 5 (May 2020) - Ghalambaz, Mohammad; Hashem Zadeh, Seyed Mohsen; Mehryan, S.A.M.; Haghparast, Amir; Zargartalebi, Hossein
Abstract: Due to the instinctive temperature-dependent heat capacity of the Nano-Encapsulated Phase Change Material (NEPCM), there is a growing interest in the potential applications of such materials in heat transfer. As such, steady-state natural convection in a porous enclosure saturated with nanofluid using NEPCMs has been investigated in this study. The cavity is assumed to have constant hot and cold temperatures at the left and right vertical boundaries, respectively, and fully insulated from the bottom and top walls. Considering the Local Thermal Non-equilibrium (LTNE) approach for the porous structure, the governing equations are first non-dimensionalized and then solved by employing the finite element Galerkin method. The impact of different parameters, such as porous thermal conductivity ( k s ), solid-fluid interface heat transfer (10 ≤ H ≤ 10 5 ), Stefan number (0.2 ≤ Ste ≤ 1), and volume fraction of nanoparticles (0.0 ≤ φ ≤ 0.05) on the patterns of the fluid and solid isotherms, streamlines and the contours of the heat capacity ratio, fusion temperature (0.05 ≤ θ f ≤ 1), local and average Nusselt numbers, and overall heat transfer ratio has been studied. It is shown that improving the porous thermal conductivity not only leads to an increase in the rate of heat transfer but also augments the fluid flow inside the cavity. For low values of the Ste, the rate of heat, transferred in the porous enclosure, is intensified. However, regardless of the amount of the Stefan number, the maximum rate of heat transfer is achievable when the non-dimensional fusion temperature is approximately 0.5. Employing NEPCMs in a highly conductive porous structure is more efficacious only when the phases are in the state of local thermal equilibrium. Nonetheless, the rate of heat transfer is higher when the Local thermal non-equilibrium is validated between the phases. Besides, for poor thermal conductivity of the porous medium like glass balls (LTE condition), adding 5% of the nano-encapsulated phase change materials to pure water can boost the rate of heat transfer up to 47% (for Ste = 0.2 and θ f = 0.5). This thermal investigation of NEPCMs shows in detail how advantageous are these nanoparticles in heat transfer and opens up an avenue for further application-based studies. Abstract : Mechanical engineering; Heat transfer; Mass transfer; Nanofluidics; Nanoparticles; Local thermal non-equilibrium; Nano-encapsulated phase change material; Nanofluid; Porous enclosure.